Competency of Midwives in Assisting Vaginal Breech Births and associated factors: A Cross-sectional study in Lower Level Health Facilities of Hoima District, Uganda. - Prossy Nandawula; Ayebare Elizabeth; Mathew Nyashanu; Michelle Telfer; Scovia Nalugo Mbalinda (Student's Journal of Health Research, 2022)
Objectives:  To assess midwives' competencies in the application of the manoeuvers for a vaginal frank breech delivery and identify factors associated with midwives' competency in delivering a vaginal frank breech. Methods:  A cross-sectional study was conducted among 143 practicing midwives who were recruited consecutively. A 30-item checklist was used to assess the midwives' competence in the application of Pinard, Loveset's, and Mauriceau Smellie Viet manoeuvers. A self-administered questionnaire was used to obtain the associated factors. Descriptive statistics were used to analyze midwives' competence. Crude Odds Ratios and their 95% confidence intervals measured the association. Results: 87.4% of midwives knew and mentioned a manoeuvre. Slightly half of 72(50.4%) study participants, with a mean score of 12.3 (SD: 2.7), were competent. Competence scores for Pinard, Loveset's, and Mauriceau Smelie Viet manoeuvres were 69.2%, 44.1%, and 30.8% respectively. Midwives who could mention any manoeuvre were 11 times more likely to be competent (Adjusted odds ratio [AOR]: 11.79, 95% CI: 2.23-58.35, P: 0.002). Midwives who felt confident were 5 times more likely to be competent (AOR: 5.95, 95% CI: 1. 23-28.80, P: 0.026).   Conclusion:  Overall midwives' competence was average. The majority were competent with the application of Pinard manoeuvre. Lovset and Mauricea Smelie Viet had below-average scores. The significantly associated factors were being able to mention any type of the manoeuvres, and reporting a feeling of confidence. These findings highlight the need for in-service vaginal breech births training, and a hands-on vaginal breech births practice to improve competence. Recommendations: The health care system should standardize the quality of midwifery practice as stated by the global standard of midwifery practice. Standard guidelines and standard operating procedures should be developed to guide the care practices in health units.